Primary photophysical and photochemical processes for hexachloroosmate(iv) in aqueous solution. Issue 2 (22nd December 2016) - Glebov, Evgeni M.; Pozdnyakov, Ivan P.; Matveeva, Svetlana G.; Melnikov, Alexei A.; Chekalin, Sergey V.; Rogozina, Marina V.; Yudanov, Vladislav V.; Grivin, Vjacheslav P.; Plyusnin, Victor F.
Abstract : The photoaquation of the OsCl6 2− complex occurs in a time interval of 80 ps via heterolytic cleavage of the Os–Cl bond. Abstract : The photoaquation of the Os IV Cl6 2− complex was studied by means of stationary photolysis, nanosecond laser flash photolysis and ultrafast kinetic spectroscopy. The Os IV Cl5 (OH) 2− complex was found to be the only reaction product. The quantum yield of photoaquation is rather low and wavelength-dependent. No impact of redox processes on photoaquation was revealed. The total characteristic lifetime of the process is about 80 ps. Three intermediates were recorded in the femto- and picosecond time domains and assigned to different Os(iv ) species. The nature of intermediates and possible mechanisms of photoaquation are discussed.